Use of a new skin colour measurement method for the investigation of relationship between skin and tooth colour - Nurullah Türker; Ulviye Şebnem Büyükkaplan; Işın Kürkçüoğlu; Burak Yılmaz (European Oral Research)
Purpose There is conflicting information about the relationship between tooth color and skin color in the literature. The aim of the present study was evaluation of the correlation between L, a, b values of skin and tooth shade using a new skin color measurement method. Materials and Methods CIELab values of teeth were obtained through measurements from the middle third of the labial surfaces on central incisors of individuals using a clinical spectrophotometer. CIELab values of the skin were measured through facial images using a software which was manufactured for present study. A statistical analysis program (SAS 9.4) was used for the analysis of the data. Kolmogorov-Smirnow test, t-test, and multivariate regression analysis were used to evaluate the data (α=0.05). Results Correlations between variables revealed that while the lowest and statistically insignificant correlations were observed with a* values of the skin, significant correlations did not exceed moderate level (p<.05). When considering regression analysis results, b* values of the skin had a statistically significant effect in describing b* values of the tooth, while L* and a* values of the skin were observed to be insufficient in describing L* and a* values of the teeth. Conclusion Results of this study suggest that different significant correlations were observed between the skin and tooth color for different L*, a*, and b parameters (p<0.05 and p<0.01). The results indicated that skin color can be used for tooth color selection in case of loss of natural teeth or when discoloration is present on existing teeth.